Implications of Traffic Analysis to Homeland Security (Journal of The Colloquium for Information Systems Security Education, 2016)
One of the biggest challenges currently faced by the Department of Homeland Security is guaranteeing cybersecurity. Each and every day some type of cybercrime occurs. Such crimes have the potential to affect the country's national security. This paper investigates the significance of internet traffic and analysis to Homeland Security. It will look at the importance of internet traffic and analysis to Homeland Security as well as encrypted traffic and its implications to cyber-security. The manner in which the U.S. has handled cybersecurity over the past twenty years and the methods that the government has used in this time period will be discussed. Encrypted mobile messaging applications will also be discussed. At the end of the discussions, solutions are recommended and a conclusion given.
Keywords: Cybercrime; Cyber Security; NSA; FBI; Terrorism; Encryption Education; Messaging Applications; Internet Traffic